TYPES OF COMMUNICATION STRATEGIES USED BY YOUNG LEARNERS IN EFL CLASSROOMS - Dewi N.L.T.; Batan I Gede; Myartawan I P.N.W (Universitas Pendidikan Ganesha, 2018)
The learner’s proficiency level in communication using English as a foreign language was indicated by their capability to make use of strategies to communicate both in written as well as spoken forms. This qualitative study focused on finding out (i) the types of communication strategies used by the students in EFL classrooms at SMP Negeri 4 Singaraja, and (ii) the students’ reasons towards the use of their communication strategies. The data were obtained from observation and focus group discussion. All data were analysed descriptively. The results of the study indicated that numerous types of strategies were used by the students when communicating in the classroom. They are the use of fillers, self-repetition, code switching, appeal for help, self-repair, asking for confirmation, massage abandonment, omission, approximation, and literal translation. Various types of reasons were expressed by the students toward the use of communication strategies such as thinking time, anxiety, and proficiency level.